The Representation of Egyptian and Syrian Governments in Bbc and Cnn Texts Regarding the Civil Wars in Egypt and Syria Silverqueen Television Advertisements - Khaerul Maaruf (Passage, 2015)
This research probes the representation of social actors in two prominent Western mass media. The Egyptian and Syrian governments are the focuses of this research. The data of this research were taken from two Western mass media, namely BBC and CNN. This research is descriptive qualitative in nature. The data includes the online news articles published in official sites of BBC and CNN. The analysis examined how social actors are excluded and included in the texts. The findings showed that BBC and CNN mostly represent the Egyptian and Syrian governments negatively. It was discovered from the excessive use of predicate with negative semantic load attached to the Egyptian and Syrian governments. Such excessive use of predicate implicates that BBC and CNN were likely to expose the bad sides of the Egyptian and Syrian governments to the world citizen. This practice appears to reflect how the two media view the two national governments.Keywords: Representation, Mass Media, Egyptian and Syrian Governments